Analytical Formulation for Electromagnetic Leakage Field to Transmission Line Coupling through Covered Apertures of Multiple Enclosures. (1st March 2017) - Hao, Jianhong; Gong, Yanfei; Jiang, Luhang; Fan, Jieqing
Abstract : An efficient analytical model has been developed for predicting the electromagnetic leakage field coupling with a lossless two-conductor transmission line (TL) through covered apertures of multiple enclosures. The analytical results have been successfully compared with those from the full-wave simulation software CST over a broad frequency range. The analytical model can be employed to analyze the effect of different factors including the position and the direction of the electric dipole, the conductivity of the conductive sheet, the quantity of the aperture, and the direction of the TL on the induced currents. Besides, it can also deal with apertures in multiple sides of the enclosures.